Ruling Women, Volume 2 - Conroy, Derval. author. aut Link
IX, 214 p.
Keywords: Ruling Women is a two-volume study devoted to an analysis of the conflicting discourses concerning government by women in seventeenth-century France. In this second volume, Configuring the Female Prince in Seventeenth-Century French Drama, Conroy analyzes over 30 plays published between 1637 and 1691, examining the range of constructions of queenship that are thrown into relief. The analysis focuses on the ways in which certain texts strive to manage the cultural anxiety produced by female rule and facilitate the diminution of the uneasy cultural reality it represents, while others dramatize the exercise of political virtue by women, explode the myth of gender-differentiated sexual ethics, and suggest alternative constructions of gender relations to those upheld by the normative discourses of sexual difference. The approach is underpinned by an understanding of theatre as fundamentally political, a cultural institution implicated in the maintenance of, and challenge to, societal power relations. Innovative and stimulating, Conroy’s work will appeal to scholars of seventeenth-century drama and history of ideas, in addition to those interested in the history of women in political thought and the history of feminism. .